The Precarious Life Situation Trap. The Case of “Zealous” Julia—A Proponent and a Victim of Neoliberal Reality - Waniek, Katarzyna (Qualitative Sociology Review, 2019)
The analysis of Julia’s (b. 1984) case, empirically grounded in the autobiographical narrative interview method, will discuss the mutual influence of the individual experiences and the collective processes that result in a precarious life situation being a stage of the trajectory of suffering process. It will be argued that the generation born between 1980-1990 that entered their adolescence period (and, at the same time, labor market) in a very specific socio-cultural context, framed by the dynamics of interrelated processes of political transformation, vibrant modernization, globalization, and, last but not least, development of neoliberal ideology, has been the first one in Poland to be exposed to the deep and overwhelming biographical changes. They have been oftentimes connected with the feeling of biographical trap and the experience of precarious balance of everyday life that—to a large extent—is a consequence of belonging to intensively multiplying social words with their divergent stocks of knowledge at hand, clashing ideologies, conflicting moral standards, dissonant rules of conducts, and expectations. Additionally, in the discussed case, I will deal with a biographical irony: Julia is both—a zealous propagator of allegedly universal attitudes of neoliberalism and a victim of this subtle mode of power. All these contradictions and tensions are clearly seen in the formal features of her (as well as many other people born in the 80’s last century) renderings, which are nonlinear, incoherent, emotionally overloaded, and full of fading-out phenomena.